2018
DOI: 10.3389/fmicb.2018.02050
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Response to Sublethal Chlorine Induced Oxidative Stress on Homologous and Heterologous Stress Adaptation

Abstract: The objective of this study was to determine the effect of chlorine induced sublethal oxidative stress against homologous and heterologous stress adaptations in five Listeria monocytogenes (Lm) strains. Lm cells were exposed to gradually increasing sublethal concentrations of total chlorine/day: 250 ppm (day 1), 270 ppm (day 2), 290 ppm (day 3), 310 ppm (day 4), 330 ppm (day 5), 350 ppm (day 6), and 375 ppm (day 7) in tryptic soy broth (TSB). Changes in minimum inhibitory concentration (MIC) and minimum bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
(44 reference statements)
2
24
1
1
Order By: Relevance
“…Both strains showed a 2.5-times decrease in susceptibility to NaOCl but this was reversible by one passage in TSB, suggesting a temporary and not genetically fixed adaptation process. Similar findings have been reported elsewhere (Bansal et al, 2018;Gao and Liu, 2014). Treatment of bacteria with sub-inhibitory concentrations of NaOCl might contribute to the emergence of antibiotic resistance (Molina-Gonz alez et al, 2014;Obe et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Both strains showed a 2.5-times decrease in susceptibility to NaOCl but this was reversible by one passage in TSB, suggesting a temporary and not genetically fixed adaptation process. Similar findings have been reported elsewhere (Bansal et al, 2018;Gao and Liu, 2014). Treatment of bacteria with sub-inhibitory concentrations of NaOCl might contribute to the emergence of antibiotic resistance (Molina-Gonz alez et al, 2014;Obe et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Impaired growth was also seen in both variants of S. aureus ATCC® 29213™. Cell wall changes after low-level exposure to NaOCl were also described for Listeria monocytogenes, another Gram-positive bacterial species (Gao and Liu, 2014;Bansal et al, 2018). Similar morphological and biological changes, including decreased growth rate, less or no hemolysis, have been described for vancomycinand teicoplanin-resistant S. aureus, adaptive resistance to amikacin, and treatment of S. aureus with erythromycin and acriflavine (Nishino, 1975;Cui et al, 2003;McCallum et al, 2006;Kawai et al, 2009;Dai et al, 2012;Yuan et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…Concerning DDAC, in agreement with DDAC MIC values ranging from 0.63 to 2.5 mg·L −1 obtained in this study, we previously showed in 31 Lm strains isolated from pig feces and pork meat that MIC values varied from 0.5 to 1.5 mg·L −1 [ 17 ]. MIC of SH mostly ranged here from 625 and 1250 mg·L −1 slightly higher than the 500 mg·L −1 SH MIC reported by Bansal et al [ 18 ] but below the 3500 mg·L −1 MIC reported by Rodriguez-Melcon et al [ 19 ]. PAC MIC values ranged here from 156.5 to 625 mg·L −1 for the 205 Lm strains, consistently with MIC values previously reported from 115 to 2713 mg·L −1 [ 20 ].…”
Section: Discussioncontrasting
confidence: 69%
“…One study reported significant correlations between biocide tolerance and antibiotic resistance in Listeria among other bacterial species isolated from seafood [86]. Unlimited exposure of the pathogen to sublethal dosages of chlorine may indirectly induce a significant tolerance to antibiotics, due to alterations in cell structure and morphology [87]. The bacteriocin nisin produced by Lactococcus lactis is one of the antimicrobial agents commonly applied in the food processing industry.…”
Section: Environmental Stress Exposurementioning
confidence: 99%